Identifying "vital attributes" for assessing disturbance–recovery potential of seafloor communities. Issue 11 (4th May 2021) - Gladstone‐Gallagher, Rebecca V.; Hewitt, Judi E.; Thrush, Simon F.; Brustolin, Marco C.; Villnäs, Anna; Valanko, Sebastian; Norkko, Alf
Abstract: Despite a long history of disturbance–recovery research, we still lack a generalizable understanding of the attributes that drive community recovery potential in seafloor ecosystems. Marine soft‐sediment ecosystems encompass a range of heterogeneity from simple low‐diversity habitats with limited biogenic structure, to species‐rich systems with complex biogenic habitat structure. These differences in biological heterogeneity are a product of natural conditions and disturbance regimes. To search for unifying attributes, we explore whether a set of simple traits can characterize community disturbance–recovery potential using seafloor patch‐disturbance experiments conducted in two different soft‐sediment landscapes. The two landscapes represent two ends of a spectrum of landscape biotic heterogeneity in order to consider multi‐scale disturbance–recovery processes. We consider traits at different levels of biological organization, from the biological traits of individual species, to the traits of species at the landscape scale associated with their occurrence across the landscape and their ability to be dominant. We show that in a biotically heterogeneous landscape (Kawau Bay, New Zealand), seafloor community recovery is stochastic, there is high species turnover, and the landscape‐scale traits are good predictors of recovery. In contrast, in a biotically homogeneous landscape (Baltic Sea), the options for recovery are constrained, the recovery pathway is thus more deterministic and the scale of recovery traits important for determining recovery switches to the individual species biological traits within the disturbed patch. Our results imply that these simple, yet sophisticated, traits can be effectively used to characterize community recovery potential and highlight the role of landscapes in providing resilience to patch‐scale disturbances. Abstract : Despite a long history of disturbance–recovery research, we still lack a generalizable understanding of the attributes that drive community recovery potential in seafloor ecosystems. To search for unifying attributes, we explore whether a set of simple traits can characterize community disturbance–recovery potential using seafloor patch‐disturbance experiments conducted in two different landscapes. We consider traits at different levels of biological organization, from the biological traits of individual species within a disturbed patch, to the traits of species at the landscape‐scale associated with their occurrence and numerical dominance across the landscape. Our results imply that these simple, yet sophisticated, traits can be effectively used to characterize recovery potential, but the scale depends on the heterogeneity in landscape biodiversity, highlighting the role of landscap es in providing resilience to patch‐scale disturbances.